2019
DOI: 10.25019/mdke/7.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Survival Strategies and Sustainability of Small and Medium Enterprises in a Volatile Environment

Abstract: Small and medium enterprises (SMEs) have been considered as one of the engines of economic growth, sustainability, and industrial development of a nation, however, the survival rate of SMEs in Nigeria has been seriously affected by the volatile environment in which they operate. The use of survival strategies has also been one of the major challenges facing the business since most people believe that strategies are only meant for large and multinational companies. This study, therefore, examines the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Previously, sustainable survival has been addressed from various perspectives. For instance, the role of corporate social responsibility in a family firm's sustainable survival (Ahmad et al, 2020); family involvement in a firm's survival (Ahmad et al, 2021); technology adoption in SMEs survival (Das et al, 2020); survival strategies in enhancing SMEs long term survival (Adebisi & Bakare, 2019); the role of creativity in enhancing SME's resilience (Zutshi et al, 2021); networking abilities in the survival of SMEs (Shah et al, 2019;Baloch & Rashid, 2022); managerial skills on SMEs' success (Ismail & Naqshbandi, 2022;Khan et al, 2022). These recent studies have revealed different factors that enhance the survival of SMEs.…”
Section: The Role Of Management Accounting In Strategic Thinkingmentioning
confidence: 99%
“…Previously, sustainable survival has been addressed from various perspectives. For instance, the role of corporate social responsibility in a family firm's sustainable survival (Ahmad et al, 2020); family involvement in a firm's survival (Ahmad et al, 2021); technology adoption in SMEs survival (Das et al, 2020); survival strategies in enhancing SMEs long term survival (Adebisi & Bakare, 2019); the role of creativity in enhancing SME's resilience (Zutshi et al, 2021); networking abilities in the survival of SMEs (Shah et al, 2019;Baloch & Rashid, 2022); managerial skills on SMEs' success (Ismail & Naqshbandi, 2022;Khan et al, 2022). These recent studies have revealed different factors that enhance the survival of SMEs.…”
Section: The Role Of Management Accounting In Strategic Thinkingmentioning
confidence: 99%
“…TCT forms an integral part of organising the modern hierarchy progress of moving products from supplier, manufacturer, wholesaler, and retailer to the ultimate consumer. The theory provides a base on which supply chain activities can be structured, organised, executed, and evaluated in a modern and innovative way to meet the express objectives of SCM (Wong & Ngai, 2022;Adebisi & Bakare, 2019). The decisions on how to undertake supply chain transactions (traditional or e-commerce), how and with whom to collaborate and integrate along the supply chain, how to evaluate suppliers and distribute goods, the make or buy decisions, application of JIT and how to make customers become an active part of firm's production process is one of the SCIPs that should be addressed from the fundamental aspects of TCT.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…These businesses account for a sizable portion of GDP. In Morocco, for example, SMEs account for 93 percent of industrial enterprises, accounting for 38 percent of production, 33 percent of investment, and 30 percent of exports (Adebisi & Bakare, 2019). In South Africa, the contribution of SMEs is far larger.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains to examine and confirm the applicability of the concept of SCRM specifically in manufacturing industries and in developing countries. (Adebisi & Bakare, 2019).…”
Section: Introductionmentioning
confidence: 99%